Pastukh I.M., Sokolova G.N., Luk’januk N.V. Nitridin with glow discharge: state and prospects. - Пастух, И.М.; Соколова, Г.Н.; Лукьянюк, Н.В. (Problems of Tribology, 2014)
The analysis of the modern state is resulted, prospects of development and application of technologies nitration with glow discharge.